Plant soil interactions alter carbon cycling in an upland grassland soil - Thomson, Bruce C.; Ostle, NIck J.; McNamara, Niall P.; Oakley, Simon; Whiteley, Andrew S.; Bailey, Mark J.; Griffiths, Robert I. (Frontiers in Microbiology, 2013)
Soil carbon (C) storage is dependent upon the complex dynamics of fresh and native organic matter cycling, which are regulated by plant and soil-microbial activities. A fundamental challenge exists to link microbial biodiversity with plant-soil C cycling processes to elucidate the underlying mechanisms regulating soil carbon. To address this, we contrasted vegetated grassland soils with bare soils, which had been plant-free for 3 years, using stable isotope (13C) labelled substrate assays and molecular analyses of bacterial communities. Vegetated soils had higher C and N contents, biomass, and substrate-specific respiration rates. Conversely, following substrate addition unlabelled, native soil C cycling was accelerated in bare soil and retarded in vegetated soil; indicative of differential priming effects. Functional differences were reflected in bacterial biodiversity with Alphaproteobacteria and Acidobacteria dominating vegetated and bare soils respectively. Significant isotopic enrichment of soil RNA was found after substrate addition and rates varied according to substrate type. However assimilation was independent of plant presence which, in contrast to large differences in 13CO2 respiration rates, indicated greater substrate C use efficiency in bare, Acidobacteria-dominated soils. Stable isotope probing revealed most community members had utilised substrates with little evidence for competitive outgrowth of sub-populations. Our findings support theories on how plant-mediated soil resource availability affects the turnover of different pools of soil carbon, and we further identify a potential role of soil microbial biodiversity. Specifically we conclude that emerging theories on the life histories of dominant soil taxa can be invoked to explain the changes in soil carbon cycling linked to resource availability, and that there is a strong case for considering microbial biodiversity in future studies investigating the turnover of different pools of soil carbon.